Gender, Corporate Risk Taking and Performance: Evidence from Indonesia - Agista Putri Prameswari (Sebelas Maret Business Review, 2016)
This study examines the effect of gender diversity in the board of director on firm leverage and financial performance. Arguably, the more the proportion of female director on board, the corporate risk taking and performance should be lower. The study uses data of listed firms in Indonesia Stock Exchange over the period of 2010-2014. The results show that the presence of female directors on the board is negatively associated with leverage. The similar result is also found on the effect of female director on the board on firm performance. Results also reveal that education background does not moderate the link between women presence on leverage and performance.